Inclusive Educational Technology - Hamburg, Ileana; Bucksch, Sascha (Archives of Business Research, 2016)
Educational technology is a collection of research approaches to improve education aiming at effective use of technological tools to facilitate learning processes. There is little literature about inclusive educational technology. In this paper we present first a literature research about inclusive educational technology fostering inclusive education and improving the quality of life by increasing participation and reducing social exclusion. Organisational factors which assure an inclusive education like competent teachers/trainers for the new roles and adequate educational technology curriculum are also presented in the paper. Inclusive educational technologies have been researched and applied by the authors also within some European projects. Within two of the projects ICT based platforms are in the development based on the research results.